Fatores de influência na urbanização em APPs - áreas de preservação permanente. O caso da APP do córrego do Gregório - São Carlos / SP - Silva, Poliana Risso da (Universidade Federal de São Carlos, 2010)
This dissertation is a theoretical study developed on urbanization processes involving Permanent Preservation Areas (APP) marginal to water bodies. The verification of a constant breach on the principle of inviolability attributed to APP, especially in urban areas, motivated this research. The objective focused on identifying and discussing the factors that influence the processes of urbanization in Permanent Preservation Areas marginal to water bodies. From the literature review, 28 factors of influence could be pointed out and organized into 08 dimensions. The case study conducted in São Carlos-SP, on the Conservation Areas of the Gregory stream, allowed the identification of influencing factors in the four analyzed periods in the history of urbanization of the municipality: 1857-1965, 1965-1979, 1979-1986 and 1986 to 2010. The results obtained in this research enabled the understanding that some permanent preservation areas, present in urban areas have been urbanized for assuming the value of urban land as defended by Villaça (2001). The value added to them is thus, not only restricted to their environmental value, but also to values of location, culture and affection among others related to the local context.
Keywords: Área de Preservação Permanente; Urbanização; Valor da terra; Engenharia Urbana; Permanent Preservation Area; Urbanization; land value; ENGENHARIAS